الاستتباع والالتزام في حروف خط الرقعة المدرسة العثمانية والبغدادية دراسة مقارنة (Journal of the College of Basic Education, 2025)
The research problem was represented by the following question: What is the following and commitment to the formations of the Ruq'ah script, the Baghdadi school and the Ottoman school as a model? While the goal came to represent the disclosure of following and commitment in the formations of the Ruq'ah script, the Baghdadi school and the Ottoman school as a model.As for the second chapter, it included three topics, the first topic dealt with the intellectual concepts of following and commitment, while the second topic was represented by the fixed and the mobile in the formations of the Ruq'ah script. The third chapter came to represent the research procedures, as the community and its sample included (28) letters, which constituted a percentage of (100%) of the total community, which were analyzed according to the research tool represented by the analysis form, and the fourth chapter concluded with a number of results, the most important of which are:1-The letter came in different between the two schools, as it appeared in the Baghdad school in a more elegant and longer form compared to the Ottoman school, which came in a shorter and thicker form.2-The lower pull also appeared in the Baghdad school in a longer form than in the Ottoman school, as in Figure (4.(3-If the form of the letter Baa has more than one formal form.4-The difference in the styles between the Baghdad school and the Ottoman school appeared, as the letter in the Baghdad school appeared more straight, the upper Haa.5- They employed design foundations to excite the recipient and give him a sense of movement by organizing the elements represented by the linear letters and words.The researchers recommended the necessity of adopting the research results as evaluative bases in the structural organization process that contributed to the restructuring of the letters of the Ruq’ah script and the strengthening of the functional, aesthetic and expressive aspects together in the formations of the Ruq’ah script among specialists from students studying the arts of calligraphy and decoration.